Diagnostic yield of targeted next generation sequencing in 2002 Dutch cardiomyopathy patients. (1st June 2021) - Alimohamed, Mohamed Z.; Johansson, Lennart F.; Posafalvi, Anna; Boven, Ludolf G.; van Dijk, Krista K.; Walters, Lisa; Vos, Yvonne J.; Westers, Helga; Hoedemaekers, Yvonne M.; Sinke, Richard J.; Sijmons, Rolf H.; Sikkema-Raddatz, Birgit; et al.
Abstract: Background: Next-generation sequencing (NGS) is increasingly used for clinical evaluation of cardiomyopathy patients as it allows for simultaneous screening of multiple cardiomyopathy-associated genes. Adding copy number variant (CNV) analysis of NGS data is not routine yet and may contribute to the diagnostic yield. Objectives: Determine the diagnostic yield of our targeted NGS gene panel in routine clinical diagnostics of Dutch cardiomyopathy patients and explore the impact of exon CNVs on diagnostic yield. Methods: Patients ( N = 2002) referred for clinical genetic analysis underwent diagnostic testing of 55–61 genes associated with cardiomyopathies. Samples were analyzed and evaluated for single nucleotide variants (SNVs), indels and CNVs. CNVs identified in the NGS data and suspected of being pathogenic based on type, size and location were confirmed by additional molecular tests. Results: A (likely) pathogenic (L)P variant was detected in 22.7% of patients, including 3 with CNVs and 25 where a variant was identified in a gene currently not associated with the patient's cardiomyopathy subtype. Only 15 out of 2002 patients (0.8%) were found to carry two (L)P variants. Conclusion: The yield of routine clinical diagnostics of cardiomyopathies was relatively low when compared to literature. This is likely due to the fact that our study reports the outcome of patients in daily routine diagnostics, therefore also including patients not fully fulfilling (subtype specific) cardiomyopathy criteria. This may also explain why (L)P variants were identified in genes not associated with the reported subtype. The added value of CNV analysis was shown to be limited but not negligible. Highlights: In patients referred for clinical genetic testing, a P or LP gene variant was detected in 22.7% of cases The yield of routine clinical diagnostics of cardiomyopathies was relatively low at 21.5% when compared to literature The added value of CNV analysis was shown to be limited at 0.1% but not negligible Daily routine diagnostics include patients not fully fulfilling cardiomyopathy subtype specific criteria